(3GdMTGFTs - (3OjSbhQjOS GdYjf RQHjs
(3ChdgG (B:s
(3hdeG cGfJ YGOI GdSQjGf aj JCdja cJHge Gf jYedhG LOhdG hLOJ ajg gPG GdLOhd hGdCYdi cd hGMO ef GdGOhjI GdebGheI s
(3BNQgG (B:s
(3TLQI GdJjf TLQI Jchf HeUQ, hdg KeQ jDcd eVYa ddeYOI hPcQ YV GdfGS Gf gPg GdTLQI cGfJ HNQSGf eGKdI , adeG fbdJ Edi eUQ aEfg JHOd WHYgG s
(3fSNI KGfjIs
(3GNJjGQGJ ef GdcJGHs
(3JHUQI GdYfhGf (B:s
(3JQLeI (B/ (3fbd s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B82 s
Keywords: (3GdWHs